A Continuous Carbon Nitride Polyhedron Assembly for High‐Performance Flexible Supercapacitors. (16th January 2017) - Lu, Chao; Wang, Dongxing; Zhao, Jingjing; Han, Song; Chen, Wei
Abstract : Flexible supercapacitors with high power density, flexibility, and durability have shown enormous potential for smart electronics. Here, a continuous graphitic carbon nitride polyhedron assembly for flexible supercapacitor that is prepared by pyrolysis of carbon nanotubes wired zeolitic imidazolate framework‐8 (ZIF‐8) composites under nitrogen is reported. It exhibits a high specific capacitance of 426 F g −1 at current density of 1 A g −1 in 1m H2 SO4 and excellent stability over 10 000 cycles. The remarkable performance results from the continuous hierarchical structure with average pore size of 2.5 nm, high nitrogen‐doping level (17.82%), and large specific surface area (920 m 2 g −1 ). Furthermore, a flexible supercapacitor is developed by constructing the assembly with interpenetrating polymer network electrolyte. Stemming from the synergistic effect of high‐performance electrode and highly ion‐conductive electrolyte, superior energy density of 59.40 Wh kg −1 at 1 A g −1 is achieved. The device maintains a stable energy supply under cyclic deformations, showing wide application in flexible and even wearable conditions. The work paves a new way for designing pliable electrode with excellent electronic and mechanic property for long‐lived flexible energy storage devices. Abstract : A continuous carbon nitride polyhedron assembly is developed using a facile pyrolysis method and is further constructed into a flexible supercapacitor with a highly ion‐conductive interpenetrating polymer network electrolyte. The high energy capacity of the device along with excellent flexibility demonstrates advancement of the novel assembly strategy, providing new insight into rational design of electrode materials for long‐lived flexible energy storage devices.